2021
DOI: 10.2967/jnumed.120.261858
|View full text |Cite
|
Sign up to set email alerts
|

Glitter in the Darkness? Nonfibrillar β-Amyloid Plaque Components Significantly Impact the β-Amyloid PET Signal in Mouse Models of Alzheimer Disease

Abstract: Objective: β-amyloid PET (Aβ-PET) is an important tool for quantification of amyloidosis in the brain of suspected Alzheimer's disease (AD) patients and transgenic AD mouse models. Despite the excellent correlation of Aβ-PET with gold standard immunohistochemical assessments, the relative contributions of fibrillar and non-fibrillar Aβ components to the in vivo Aβ-PET signal remain unclear. Thus, we obtained two murine cerebral amyloidosis models that present with distinct Aβ plaque compositions and performed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…For all mice, behavioral testing after the terminal PET scan was followed by immunohistochemical and biochemical analyses of randomized hemispheres. The TSPO-PET arm of the study and detailed analyses of neuroinflammation imaging are reported in a separate manuscript focusing on the predictive value of TSPO-PET for outcome of PPARγ-related immunomodulation ( Biechele et al, 2022 ). The sample size estimation of the in vivo PET study was based on previous experience and calculated by G*power (V3.1.9.2, Kiel, Germany), assuming a type I error α = 0.05 and a power of 0.8 for group comparisons, a 10% drop-out rate per time-point (including TSPO-PET), and a treatment effect of 5% change in the PET signal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all mice, behavioral testing after the terminal PET scan was followed by immunohistochemical and biochemical analyses of randomized hemispheres. The TSPO-PET arm of the study and detailed analyses of neuroinflammation imaging are reported in a separate manuscript focusing on the predictive value of TSPO-PET for outcome of PPARγ-related immunomodulation ( Biechele et al, 2022 ). The sample size estimation of the in vivo PET study was based on previous experience and calculated by G*power (V3.1.9.2, Kiel, Germany), assuming a type I error α = 0.05 and a power of 0.8 for group comparisons, a 10% drop-out rate per time-point (including TSPO-PET), and a treatment effect of 5% change in the PET signal.…”
Section: Methodsmentioning
confidence: 99%
“…Components with an Eigenvalue >1.0 were extracted and a varimax rotation was selected. Water maze results were also used as an endpoint in the dedicated manuscript on serial TSPO-PET in both cohorts ( Biechele et al, 2022 ). For immunohistochemistry quantifications GraphPad Prism (GraphPad Software, San Diego, California, United States) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, signal loss due to atrophy could be another confounder of the observed decreased SUVr. Then, the altered plaque morphology in terms of reduced Aβ plaque density could also lead to a reduced signal in PET (Biechele et al, 2021). In this regard, we noted that diffuse and vascular Aβ occurring at cSS sites provides fewer tracer binding sites when compared to cored Aβ plaques which could, in turn, hamper the detection by PET.…”
Section: Discussionmentioning
confidence: 91%
“…One of the unsolved question in Aβ imaging is the detection towards small forms of A aggregates. Biechele et al recently indicated that the non-fibrillar Aβ (positive for 3552 antibody) in addition to the Thiazine red stained fibrillar Aβ significantly impacted the [ 18 F]florbetaben PET signal in App NL-G-F and APP/PS1 mice from 3-12 month-of-age [68].…”
Section: Amyloid Imagingmentioning
confidence: 99%
“…RN wrote the manuscript and approved the submission. APP/PS1 mice [40,60,82,86,[246][247][248] 3×Tg mice [249] APP23 mice [37,60,190] Aged non-human primate TASTPM mice [250] APP/PS1 mice [73,251] [ 18 F]florbetaben, AV-1 PS2APP mice [61,252] APPswe mice [61,253] App NL-G-F mice [68,192,197,252,254] APPswe/PS1G384A mice [61] APP-SL70 mice [252,255] TgF334 rats [152] APP/PS1 mice [61,68,82,256] [ 11 C]AZD2184 APPswe mice [244] APP/PS1 mice [257] [ 18 F]flutafuranol AZD4694, NAV4694…”
Section: Author Contributionsmentioning
confidence: 99%